Astudy on antioxidant enzyme activities and gene expression in different barley genotypes under drought stress - Alghabari, Fahad Mohammed (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2023)
Barley is an ecologically important crop with wide adaptability in varied climatic conditions.The current study was conducted with the objective of testing the performance of different barley genotypes (Jau-87, Sanober-96, Frontiers-87 and Soorab-96) at enzymatic (superoxide dismutase, peroxidase and catalase) and genetic levels (HvDREB3, HvWRKY42, HvHsfB2c and HvERF4) under drought stress. Atri-replicate pot experiment was conducted underglasshouse conditions using a randomized complete block design (RCBD). The data collected for antioxidant enzymes were subjected to statistical analysis using Statistix8.1 program, while gene expression analysis was done using RT-PCR and expression was normalized using HvActin1-expressing gene. All genotypes recorded an increase in the activities of antioxidant enzymes due to drought stress. Correspondingly, all genotypes showed over-expression of all drought-associated genes under drought treatment compared to the control condition. Furthermore, all genotypes depicted complete parallelism in the expression of drought-associated genes and increased activity of antioxidant enzymes due to the involvement of these genes in regulating the metabolic pathways involved in the production of these antioxidant enzymes. Overall, the current study proved the complementary performance of all four genotypes in perspective of antioxidant and genetic responses; hence they can further serve as a valuable source for elucidating the dynamics of drought stress tolerance.